A Study on Stress management Among the Employees of Nationalised Banks - Goel, Anuj; Kamboj, Akshita (Journal of Commerce and Trade, 2014)
Organizational life is quite stressful. Work pressures, tight schedules, meetings that never seem to end on time, unhelpful colleagues, critical bosses, incompetent subordinates and a host of other irritating factors may all have a cumulative effect in making the lives of modern-day executives quite miserable. As we all know, stress is the body’s reaction to any demand made on it. Perception of events, whether positive or negative, activates stress. Banking, like other services, has become one of the highly competitive sectors in India. The banking organizations, since the beginning of this decade, have been facing greater challenges in terms of technological revolution, service diversification and global banking. Stress is unavoidable on the part of the employees as the systems, procedures; techniques are getting complicated with the use of advance technology. Every employee cannot cope with such rapid changes taking place in the jobs. This will lead to arising of stress among employees. An attempt has been made through this research paper to know the reasons of stress among the bank employees and the ways used by employees to cope with the stress generated at workplace. It is found that maximum number of employees in banks remains in stress. Majority of the employees try to find solution to relieve them from stress. Also the measures are also suggested in the paper to overcome stress that affects their physical and mental health.